Human embryonic stem cell-derived Sertoli cells as an immune modulator of cell transplantation therapy in a diabetic mice model - Jeoung Eun Lee; Chang Woo Lee; A-Reum Han; Jina Kim; Dong Ryul Lee (Stem Cell Research & Therapy)
Abstract Objective Sertoli cells (SCs) are somatic cells that are a part of the seminiferous tubules in the testes and support germ cell development and maturation. Additionally, SCs play another role in protecting male germ cells from immune destruction via the formation of the blood-testis barrier and the secretion of several immunoregulatory factors. Based on these characteristics, SCs have been suggested to create a tolerogenic environment to protect co-transplanted cells as immune modulators. Because mature SCs are quiescent somatic cells and show lower proliferation activity in vitro, it is difficult to obtain the number of human cells needed for clinical applications. Materials and methods We established a protocol for mass production of SCs from human ESCs (hESC-SCs) and their functional properties were analyzed in vitro and in diabetic-induced mice after their co-transplantation with human insulin-secreting cells. Results hESC-SCs were successfully produced via a stepwise differentiation protocol. In addition, a mass culture method was established to secure the number of hESC-SCs available for cell therapy. hESC-SCs obtained from in vitro derivation highly express marker genes of SCs, such as GATA4, SOX9, CLDN11, and AR, and have shown immune-modulation activity similar to that of human bone marrow-mesenchymal stem cells. In diabetic-induced mice subcutaneously co-transplanted with EndoC-βH1 cells (insulin-secreting cells) and hESC-SCs, lower blood glucose levels were maintained for 6 months than in those transplanted with EndoC-βH1 cells alone. Conclusions We believe that hESC-SCs could be useful tool for securing cell therapy to treat human diseases in the future.